Aseptic complications of total knee replacement and treatment options. Issue 1 (February 2021) - Bhamber, Nivraj Singh; Waterson, Ben; Toms, Andrew
Abstract: Total knee replacement surgery is a commonly performed procedure with good improvement in the quality of life for patients. However, there are a number of complications from surgery than can have adverse outcomes for patients. Although infection is a disastrous complication of orthopaedic surgery, aseptic complications occur more commonly. We also aim to review these complications and give the principles and strategies for preventing and treating them. This article discusses early perioperative problems such as acute nerve and vessel injuries, thromboembolism, wound problems and extensor mechanism problems. It also reviews the pertinent points of later postoperative complications such as persistent swelling, pain, loosening and stability problems.